Предмет: Математика,
автор: fgssgw12
Помогите решить задание номер 4! Преобразовать выражение
Приложения:
Ответы
Автор ответа:
1
(2xy/(4x^2-9y^2) + y/(3y-2x))*(1- (2x-3y)/(2x+3y))^(-1)=
(2xy/((2x-3y)(2x+3y)) - y/(2x-3y)) * ((2x+3y-2x+3y)/(2x+3y))^(-1)=
((2xy - 2xy -3y^2)/((2x-3y)(2x+3y)))*((2x+3y)/6y)=
-3y^2/((2x-3y)(2x+3y))*((2x+3y)/6y)=
-y/2(2x-3y)=-y/(4x-6y)
Похожие вопросы
Предмет: Другие предметы,
автор: ermilova5509
Предмет: Биология,
автор: Аноним
Предмет: Математика,
автор: thekozume
Предмет: Математика,
автор: sushka149
Предмет: Алгебра,
автор: ilen99518